LEGAL STATUS OF ADOPTED CHILDREN IN THE CIVIL INHERITANCE LAW BASED ON ARTICLE 832 OF THE CIVIL LAW BOOK - Wulan Agustini; Gunawan Djajaputra (RADJA PUBLIKA, 2023)
Adoption of children based on Article 1 number 2 of Government Regulation Number 54 of 2007 concerning the Implementation of Adoption states that: